Kontroversiel relevans: Tal der virker, er tal der splitter - Meilvang, Hjalte (Politik, 2017)
Statistics and indicators are key tools for the use of knowledge in policy, management and governance. In the so-called evaluation wave (Dahler-Larsen and Kristiansen 2015) and evidence-based-policy movement (Bhatti et al. 2006; Krogstrup 2011) numbers contribute ostensibly objective descriptions and the possibility of explicit comparison. However, indicators should not be regarded as unproblematic value-free knowledge – but must be seen as politically efficacious when we have ‘trust’ in them through their seemingly uncontroversial objectivity (Porter 1995). However, it is difficult for an indicator to be at the same time politically significant and uncontroversial. Numbers and statistics become relevant when they are used. But use increases the risk of controversy. Numbers that work, work in ways that will be contrary to some. Through an analysis of standardized testing in Danish schools, this article explores how the politics of numbers unfolds between relevance, where numbers become useful for management and governance – and the controversy this relevance causes.